Chemical and sensory properties of young cabernet sauvignon and marselan wines from subregions on the eastern foothills of helan mountains in ningxia, China: Terroir effect - Xue Zhang; Hui Yang; Na Liu; Jian Sun; Ruijia Yao; Fangzhou Shi; Jiming Li; Wenguang Jiang; Hongying Li; Qingchen Zhang; JunXiang Zhang (Food Chemistry: X)
This study aimed to analyze the characteristics of Cabernet Sauvignon (CS) and Marselan (M) wines from different subregions on the eastern foothills of Helan Mountain. UHPLC–ESI–Q–ToF and HS–SPME–GC–MS were employed to analyze the metabolic properties of the wines, and QDA was combined for sensory characterization. The results indicated that chromaticity, total phenols, ethyl isobutyrate, n-decanoic acid, (−)-epigallocatechin, and epigallocatechin were key indicators for distinguishing CS wines from different subregions, whereas total acids, total phenols, hexanol, ethyl butyrate, protocatechuic acid, and (+)-catenin were key indicators for distinguishing M wines from different subregions. The richness and coordination of fruit, floral, dried fruit, spice, and green flavors in the wine were key indicators determining the flavor characteristics of wine in winemaking area. The key compounds with aroma of green, fruity, and floral that determine the core aroma, aroma coordination, and elegance of wine in the winemaking area include cis-2-exen-1-ol, ethyl palmate, octanoic acid, and n-decanoic acid.